National Early Warning Score Does Not Accurately Predict Mortality for Patients With Infection Outside the Intensive Care Unit: A Systematic Review and Meta-Analysis - Zhang, Kai; Zhang, Xing; Ding, Wenyun; Xuan, Nanxia; Tian, Baoping; Huang, Tiancha; Zhang, Zhaocai; Cui, Wei; Huang, Huaqiong; Zhang, Gensheng (Frontiers in Medicine, 2021)
Background: The prognostic value of National Early Warning Score (NEWS) in patients with infections remains controversial. We aimed to evaluate the prognostic accuracy of NEWS for prediction of in-hospital mortality in patients with infections outside the intensive care unit (ICU). Methods: We searched PubMed, Embase, and Scopus for related articles from January 2012 to April 2021. Sensitivity, specificity, and likelihood ratios were pooled by using the bivariate random-effects model. Overall prognostic performance was summarized by using the area under the curve (AUC). We performed subgroup analyses to assess the prognostic accuracy of NEWS in selected populations. Results: A total of 21 studies with 107,008 participants were included. The pooled sensitivity and specificity of NEWS were 0.71 and 0.60. The pooled AUC of NEWS was 0.70, which was similar to quick Sequential Organ Failure Assessment (qSOFA, AUC: 0.70) and better than Systemic Inflammatory Response Syndrome (SIRS, AUC: 0.60). However, the sensitivity (0.55) and AUC (0.63) of NEWS were poor in elder patients. The NEWS of 5 was more sensitive, which was a better threshold for activating urgent assessment and treatment. Conclusions: The NEWS had good diagnostic accuracy for early prediction of mortality in patients with infections outside ICU, the sensitivity and specificity were more moderate when compared with qSOFA and SIRS. But insufficient sensitivity and poor performance in elder population may have limitations as an early warning score for adverse outcomes. The NEWS should be used for continuous monitoring rather than a single time point predictive tool.